A hybrid piezoelectric-electromagnetic wave energy harvester based on capsule structure for self-powered applications in sea-crossing bridges. (November 2021) - Qi, Lingfei; Li, Hai; Wu, Xiaoping; Zhang, Zutao; Duan, Wenjun; Yi, Minyi
Abstract: The ocean is a huge kinetic energy field with considerable energy harvesting potential. Harvesting renewable ocean wave energy and using it to power electric facilities such as sensors for sea-crossing bridges in real time could be an effective strategy to promote sustainable development of the oceans. In this paper, we propose a piezoelectric-electromagnetic wave energy harvester (PEWEH) based on a sealed capsule structure for self-powered applications in sea-crossing bridges. The proposed system consists of three main components: piezoelectric module, electromagnetic module, and energy storage module. The piezoelectric module is mainly composed of two piezoelectric sheets which can be deformed by continuous wave motion to generate electricity. The electromagnetic module includes a fixed coil and a core that moves back and forth to cut the magnetic line to generate electricity. The electrical energy recovered by the piezoelectric module and electromagnetic module will be stored in the energy storage module after being rectified and stabilized. Experiment results showed that output voltage up to 7 V and power of 162 mW can be obtained by the PEWEH, validating that the proposed wave energy harvesting system is promising for self-powered applications in low-power monitoring sensors for sea-crossing bridges. Graphical abstract: Image 1